2014
DOI: 10.1371/journal.pone.0094217
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Single Dose of Ferric Carboxymaltose in Fatigued, Iron-Deficient Women – PREFER a Randomized, Placebo-Controlled Study

Abstract: BackgroundUnexplained fatigue is often left untreated or treated with antidepressants. This randomized, placebo-controlled, single-blinded study evaluated the efficacy and tolerability of single-dose intravenous ferric carboxymaltose (FCM) in iron-deficient, premenopausal women with symptomatic, unexplained fatigue.MethodsFatigued women (Piper Fatigue Scale [PFS] score ≥5) with iron deficiency (ferritin <50 µg/L and transferrin saturation <20%, or ferritin <15 µg/L) and normal or borderline hemoglobin (≥115 g/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
102
3
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(123 citation statements)
references
References 39 publications
9
102
3
9
Order By: Relevance
“…It should be noted that study participants were not blinded to treatment and, therefore, the assessment of quality-of-life could have been influenced by subject bias. However, our findings are in accordance with those from a previous randomized, controlled trial in which FCM was found to significantly improve symptomatic fatigue in iron-deficient women [21]. Increased vitality can be of particular benefit in coping with the extreme physical stresses experienced by women during pregnancy and childbirth.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It should be noted that study participants were not blinded to treatment and, therefore, the assessment of quality-of-life could have been influenced by subject bias. However, our findings are in accordance with those from a previous randomized, controlled trial in which FCM was found to significantly improve symptomatic fatigue in iron-deficient women [21]. Increased vitality can be of particular benefit in coping with the extreme physical stresses experienced by women during pregnancy and childbirth.…”
Section: Discussionsupporting
confidence: 92%
“…Pregnant women aged ≥ 18 years, in their second or third trimester (gestational weeks [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] and with serum ferritin levels ≤ 20 ng/mL and IDA [defined as hemoglobin (Hb) 8.0-10.4 g/dL for gestation weeks [16][17][18][19][20][21][22][23][24][25][26] or Hb ≤ 11.0 g/dL for gestation weeks 27-33] were eligible for this study. Women were excluded if they had a significant bleed or surgery within 3 months prior to screening, received a blood transfusion, erythropoietin treatment, oral iron (unless the dose was ≤ 100 mg iron per day) or parenteral iron treatment during the month prior to screening, or were anticipated to need a blood transfusion during the study period.…”
Section: Participantsmentioning
confidence: 99%
“…FCM, the most recently approved formulation, has been safely administered as a 1,000-mg infusion over 15 min [66], and is approved in Europe at this dose. In the US, its current approval is for not more than 750 mg administered over the same interval.…”
Section: How We Treatmentioning
confidence: 99%
“…7 The adverse effects like rashes (in form of allergy), vomiting, breathlessness and myalgia were also seen in the population who were involved in the clinical trial phases but these adverse reaction were rare (<1%), which is also known as type 1 Hypersensitivity reactions. 3,8 A fast iron infusion rate is a well-recognized risk factor, one possible explanation being the rapid increase in labile free iron.…”
Section: Lab Parametersmentioning
confidence: 99%